Indonesian International Scientific Publication Trend, 2015-2019 - Prakoso Bhairawa Putera; ‪Parama Tirta Wulandari Wening Kusuma‬; Suardi Kadang (Pustabiblia: Journal of Library and Information Science, 2021)
This article discusses trends in Indonesia's international scientific publications in the 2015-2019 period. Indonesian international scientific publications are sourced from the Scopus data base and the data were analyzed using a bibliometric approach with visualization of VOSviewer version 1.6.15. The results show that Indonesia's international publications during the 2015-2019 period experienced a significant increase, namely 8,373 publications in 2015 to 46,028 publications in 2019, or an increase of 5.5 times from the publication in 2015. Munir, A was recorded as the most productive writer with produced 239 publications during those five years, followed by Sarno, R (221 publications), Purnomo, MH (207 publications), Hidayanto, A.N. (182 publications), and Rahim, R. (167 publications). Universitas Indonesia as the institution with the most publications with 11,661 articles, followed by the Bandung Institute of Technology (8,961 publications), Gadjah Mada University (7,369 publications), Sepuluh Nopember Institute of Technology (5,096 publications), and Diponegoro University (4,997 publications). Other results show that most (50.9%) publications produced by authors from Indonesia are published in Scopus indexed international proceedings (such as the IOP Conference Series, AIP Conference Proceedings, MATEC Web of Conferences, E3S Web of Conferences, and ACM International Conference Proceedings. Series), and articles in international journals (46.7%). The most collaborators came from Malaysia (5,780 articles), Japan (5,373 articles), Australia (3,253 articles), the United States (2,849 articles), and England (2,194). Engineering is the most predominantly published research field, this is confirmed by the top 3 sources of publications, namely the Journal of Physics Conference Series (10.61%), IOP Conference Series Earth and Environmental Science (8.28%), and IOP Conference Series Materials Science and Engineering (6.33%). The conclusion of this study shows that there is a significant increase in Indonesian international publications indexed by Scopus of 549.71% during the 2015-2019 period. This significant increase stems from the publication of articles by Indonesian authors in international proceedings.